Management outcome of blunt renal trauma in a tertiary level hospital of Bangladesh - Kabir, MD Golam; Kamal Basu, Banga; Ahmed, Masud; Hasan, Mahmud; Hossain, Moajjam; Islam, Tarikul (Mediscope, 2021)
Background: The kidney is the commonly injured genitourinary and abdominal organ. Renal injuries are classified by their mechanism: blunt or penetrating. Failure to perform appropriate evaluation and treatment of these injuries may result in significant long term patient morbidity. Objective: To evaluate blunt renal trauma cases at a tertiary level hospital to find out management practices along with patient outcomes. Methods: This prospective observational study was conducted in the Department of Urology of Dhaka Medical College Hospital during the period of January 2011 to December 2012 to observe the management outcome of blunt kidney injuries. Sampling technique was purposive and sample size was 110. After management of blunt kidney injury by either conservatively or by surgical means, some patients were followed up for 2 years and others for less than 2 years. Results: In this study, 90.1% patients were diagnosed and staged by contrast enhanced CT scan. Most of the early grade injuries (grade I-III) were treated conservatively and outcome in terms of surgical conversion and short term complications were favourable. Few bluntly injured grade IV and V required operative interventions. Overall nephrectomy rate was only 3.6%. Haemodynamic instability, associated organ injury, higher grade injury - all were predictive indicators of operative interventions. The study showed that rates of complications were more in higher grade injury, with concomitant other organ injuries and in patients who required blood transfusion (indicator of hemodynamic instability). Conclusion: Most of the blunt kidney injuries can be managed in conservative way with favourable outcome. Mediscope 2021;8(2): 103-111